Boosting skills for all in the Netherlands - Kierzenkowski, Rafal (OECD Publishing, 2016)
Strong and adequate skills are essential to support workers' productivity and to ensure robust employment outcomes. Developing workers' skills would also increase their personal satisfaction and wages, contributing in making growth more inclusive. The Netherlands performs well in terms of competences of a large part of the population. Moreover, the country has been successful in adjusting the required level of skills over time. The education system plays a key role in developing skills and achieves good results, but there is room to make vocational education and lifelong learning less job-specific to better adapt to new economic trends. There is scope to use more effectively existing skills at work of youth entering the labour market and entrepreneurs, and to reduce labour market mismatches. Another challenge is to help some people to acquire skills by facilitating their labour market integration - in particular first- and second-generation immigrants, long-term unemployed, and people with low educational attainment and health problems -, which requires stronger targeted active labour market policies
Keywords: Economics; Netherlands